2014
DOI: 10.5901/mjss.2014.v5n10p163
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Internal Controls in Fast Moving Small Medium and Micro Consumer Goods Enterprises within the Cape Peninsula

Abstract: South African Small Medium and Micro Enterprises (SMMEs) play an important role in terms of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…Instrumen berupa kuisioner yang berisi sejumlah pertanyaan dan pernyataan untuk dijawab dan disetujui oleh para responden penelitian. Secara umum kuisioner ini digunakan untuk memperoleh data kuantitatif tentang implementasi mekanisme good corporate governance di UKM dengan memberikan persepsi atas pernyataan-pernyataan persetujuan dengan skala likert dari tingkat tidak setuju (skor=1) sampai dengan sangat setuju (skor=5) seperti telah dilakukan oleh Siwangaza et al (2014) dan pertanyaan-pertanyaan dengan jumlah aktivitas dengan skala interval rendah (skor=1) sampai dengan tinggi (skor=4). Instrumen divalidasi oleh ahli manajemen (2 orang) dan pelaku UKM (2 responden).…”
Section: Metode Pengumpulan Dataunclassified
“…Instrumen berupa kuisioner yang berisi sejumlah pertanyaan dan pernyataan untuk dijawab dan disetujui oleh para responden penelitian. Secara umum kuisioner ini digunakan untuk memperoleh data kuantitatif tentang implementasi mekanisme good corporate governance di UKM dengan memberikan persepsi atas pernyataan-pernyataan persetujuan dengan skala likert dari tingkat tidak setuju (skor=1) sampai dengan sangat setuju (skor=5) seperti telah dilakukan oleh Siwangaza et al (2014) dan pertanyaan-pertanyaan dengan jumlah aktivitas dengan skala interval rendah (skor=1) sampai dengan tinggi (skor=4). Instrumen divalidasi oleh ahli manajemen (2 orang) dan pelaku UKM (2 responden).…”
Section: Metode Pengumpulan Dataunclassified
“…However, smaller businesses will be more vulnerable to these changes as opposed to their larger counterparts. This is especially the case since SMMEs do not have sophisticated and durable infrastructures (Siwangaza, Bruwer, Smit & Ukpere, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hence it is no surprise that SMMEs are regarded as major role players -as catalysts -in the development of any country (Shah & Khedkar, 2006). Albeit the above Siwangaza, et al (2014) noted that South African SMMEs do not have a good 'track record' when it comes to remaining going concern enterprises. In the early 2000's Van Eeden et al (2003) found that between 70% and 80% of South African SMMEs failed within their first 3 years of existence.…”
Section: An Overview Of South African Smmesmentioning
confidence: 99%